The preparation, and structural and multiferroic properties of B-site ordered double-perovskite Bi2FeMnO6. Issue 22 (30th May 2017) - Sun, Lin; Fang, Yue-Wen; He, Jun; Zhang, Yuanyuan; Qi, Ruijuan; He, Qing; Huang, Rong; Xiang, Pinghua; Tang, Xiao-Dong; Yang, Pingxiong; Chu, Junhao; Chu, Ying-Hao; et al.
Abstract : B-site ordered Bi2 FeMnO6 films have been fabricated and found with good ferroelectricity and spin-glass state. Abstract : We report the structural, magnetic, and ferroelectric properties of double-perovskite Bi2 FeMnO6 in which Fe 3+ and Mn 3+ cations are present with alternative ordering along the [111] direction. High-flux synchrotron X-ray diffraction and high resolution transmission electron microscopy show that the pseudo-cubic lattice of Bi2 FeMnO6 consists of alternatively corner-shared octahedra of FeO6 and MnO6 . In the highly ordered Bi2 FeMnO6 thin films, the unusual spin-glassy magnetic state is observed below 18 K by a superconducting quantum interference device, and this is ascribed to the magnetic frustration at the [111] Fe 3+ and Mn 3+ planes as indicated by X-ray magnetic circular dichroism measurements. Combining with the orbital model analysis based on Goodenough–Kanamori–Anderson rules, first-principles calculations and Monte Carlo simulations suggest that magnetic frustration is dominated by the long-range second nearest neighboring antiferromagnetic interactions of Fe 3+ –Fe 3+ and Mn 3+ –Mn 3+ and leads to the surprisingly weak magnetism. On the other hand, robust room-temperature ferroelectricity in Bi2 FeMnO6 films is confirmed by piezoelectric force microscopy through electrically switching the polarization state and the ferroelectric retention.